A comparison of long-term outcomes between narrow and broad QRS complex patients treated with cardiac resynchronization therapy. Issue 3 (1st June 2016) - Yap, Lok Bin; Nguyen, Son Thai Bin; Qadir, Faisal; Keng, Soot; Muhammad, Zulkeflee; Koh, Kok Wei; Ali, Zunida; Tay, Giat Seng; Daud, Azlina; Said, Amirzua; Sahat, Noorasyikin; Rebo, Rosila; et al.
Abstract : Introduction There are few registries for narrow QRSd ≤ 120 ms patients treated with cardiac resynchronization therapy (CRT). We report longterm outcomes for patients with narrow QRSd ≤ 120 ms compared to broad > 120 ms patients. Methods The study included 297 heart failure patients with a CRT device implanted from 2001 to 2012. LV reverse remodelling (reduction in LV end-systolic volume, LVESV, of < 15%), rates of hospitalization for heart failure and all-cause mortality were studied. Results There were 121 narrow QRSd ≤ 120 ms and 176 QRSd < 120 ms patients. There was no difference in LVESV (> 15%) reduction comparing narrow and broad QRSd groups (relative risk 0.87, 95% CI 0.69-1.09, P = 0.24) between 6 to 18 months. The relative risk for hospitalization comparing narrow and broad QRSd patients was 1.18 (95% CI 1.06-1.30, P < 0.01). With a mean follow-up of 3.9 years, there were 31 (25.6%) deaths in the QRSd ≤ 120 ms group and 42 (23.8%) deaths in the QRSd < 120 ms group. Survival analysis showed no significant difference between the two groups [hazard ratio, HR 1.05 (0.66-1.67), P = 0.85]. Conclusions We found that narrow QRSd ≤ 120 ms patients treated with CRT have a similar rate of LV reverse remodelling and mortality, but a higher rate of hospitalization when compared to broad QRSd < 120 ms patients.